Alignment between the cognitive demands of the written and assesed trigonometry curricula in South Africa - Molepo, Nathaniel Samuel (My University, 2017)
This study investigated the degree of alignment of cognitive demand between the written and the assessed trigonometry curriculum in South Africa. The written curriculum describes the content as it is depicted in the textbook. The assessed curriculum on the other hand refers to the content knowledge upon which student learning is measured. The issue that the study sought to understand is: what type of cognitive demands are implied in the instructional tasks around the general solutions of trigonometric equations in two Grade 12 NCS (CAPS) prescribed mathematics textbooks and in the assessment tasks in the NSC examinations. The study also examined the extent to which the cognitive demands of tasks in each of these curriculum documents align. Anderson (2002) curriculum alignment framework was used as a conceptual framework for the study. The study was a qualitative case study, the methodology of which was framed by Survey of Enacted Curriculum by Porter (2002). The SEC instrument was used to assign judgements of the cognitive demand of the tasks in the textbooks and the NSC examinations. Findings indicate that the degree of alignment between tasks of textbooks and NSC examinations varied. Most of the tasks presented in the most used textbook (Platinum Mathematics Grade 12) corresponded to the categories that exhibited lower order cognitive demands. These were mainly associated with ‘memorisation’ and ‘perform procedures’ of Porter’s (2002) cognitive demand framework. However tasks in the NSC examinations were basically at the higher order level of Porter’s (2002) framework. A reduced level of alignment was noted between the cognitive demands of tasks in Platinum Mathematics Grade 12 textbook and the tasks in the NSC examinations. In terms of tasks from Classroom Mathematics Grade 12 textbook and tasks in the NSC examinations, there was a strong alignment of cognitive demands between each of the these curriculum documents. The study recommended that those charged with the responsibilities of curricula management should be mindful of the fact that if students are expected to learn skills associated with higher order cognitive demands, then it is essential that all forms of curricular documents, particularly prescribed textbooks that guides teaching and learning on a daily basis should make such skills available, If not, then the students may be deprived from learning the envisaged skills.
A research report submitted in partial fulfilment of the requirements for the degree of Masters of Science to the Faculty of Science, University of the Witwatersrand, Johannesburg, 2017
Keywords: Mathematics--Study and teaching (Secondary)--South Africa; Trigonometry--Study and teaching (Secondary)--South Africa